Design and Simulation of a 25MW Solar Power Plant in Baku City - Guliyev, Ilgar (ADA University, 2023)
Recent advancements in technology have facilitated the development of power generation systems that harness solar energy through the utilization of floating photovoltaic (FPV) systems. The utilization of floating photovoltaic systems is both a new and prevalent technique for incorporating PV modules within water frameworks, thus preserving land area. Additionally, the electrical efficiency of a solar system exhibits a decline as the temperature rises. Thus, in order to enhance efficiency, it is necessary to cool the photovoltaic (PV) module by implementing a heat removal mechanism. The water below naturally cools FPV projects, providing them with an advantage. This study explores the feasibility of implementing floating solar panels in Boyukshor Lake, located in Baku City. The proposed power plant is a grid-tied system with a capacity of 25 MW. The site exhibits convenient accessibility and adequate water depth, which ranges between 3.40 meters and 4.20 meters. The FPV energy project in Boyukshor Lake involves the assessment of several factors, such as panel positioning, solar panel efficiency, and surface area availability. The construction of the single line diagram is determined by considering the solar module and inverter as independent variables. The investigation selected two types of PV modules and string inverters based on their parameters. The analysis demonstrated the mean global horizontal irradiance (GHI) for the specified region is 1523.4 kilowatt-hours per square meter per year. The master thesis consists of three simulations. In the first and second cases, the chosen arrangement of components for the floating solar power plant comprises 45791 panels with a total power output of 29764 kW. The panels are organized into 29 series and accompanied by 1579 string solar panels. The first and second cases include a 3125 kW inverter, while the third case will be simulated with a 100 kW inverter. In the simulation, both AC and DC cables are utilized. The design exhibits anticipated system performance metrics, including a performance ratio, system efficiency, and capacity factor. Also, this study provides an economic and environmental evaluation of the above-mentioned simulations. These considerations contribute to the development of a complete model that accurately predicts the entire electricity generation of the Boyukshor floating PV power plant. As a result, this method of producing electricity involves analyzing simulated data, looking at the theoretical underpinnings, evaluating the capital investment, operational costs, and maintenance costs, as well as assessing its numerous advantages.
Keywords: Floating photovoltaic power systems--Design and construction; Solar energy--Floating systems; Solar energy--Efficiency--Photovoltaic systems; Solar power generation--Performance evaluation; Azerbaijan--Renewable energy development; Azerbaijan--Solar energy projects; IT and Engineering